PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM MAGRIB MENGAJI PADA ANAK-ANAK DI DESA AEK NAULI KECAMATAN HULU SIHAPASKABUPATEN PADANG LAWAS UTARA - Siti Kholijah; Sarah Citrasari, Cahaya Rangkuti, Trini Damayanti, Irwan Efendi Hsb, Nur Jannah Angriani, Muhamad Ri (Adisam Publisher, 2025)
Objective. Community Service Program (Kuliah Kerja Nyata/KKN) is a form of community engagement carried out by students under the guidance of lecturers. This engagement aims to foster synergy between universities and communities, particularly by enabling students to apply the knowledge they have gained during their academic studies. This research aims to assess the effectiveness of Magrib Mengaji within the context of community engagement. The study involves various individuals from diverse communities participating in this community service effort. The research method employed is Participation Action Research (PAR). The results of this community engagement research demonstrate a significant improvement in children's ability to read the Qur'an after participating in the Magrib Mengaji program. This program proves effective in enhancing children's Qur'anic reading skills in Desa Aek Nauli. Furthermore, Magrib Mengaji also holds great potential for enhancing children's understanding of religious values, accompanied by social, moral, and cultural values through these Magrib Mengaji activities.